Evaluación de embriones a congelación lenta y vitrificación en bovinos ( Bos taurus ) en el laboratorio de biotecnología de reproducción de la carrera de medicina veterinaria y zootecnia de la Universidad Técnica de Cotopaxi - Esparza Álvarez, Diego Armando (2015)
This research aims to determine the progress made regarding bovine embryos by slow freezing and vitrification n in the laboratory of reproductive biotechnology at the University, these techniques have evolved in procedures simpler, practical and less expensive freezing, one is vitrification, solidification process, in which a highly concentrated solution which does not crystallize during freezing is used, while the viscosity increases with decreasing temperature until the formation of an amorphous glass-like solid. For embryos withstand osmotic shock, to be balanced with a lower concentration cryoprotectant solution before exposure to the vitrification solution for further freeze. Has published many embryos vitrification procedures, using different cryoprotectants, concentration, volume, method of addition, temperature, exposure time, rate of freezing, thawing and dilution, to maintain the function, normal structure and embryo viability....